Effects of agricultural extension and environment-related practices on technical effiency of paddy farmers in the central region of Thailand - Taraka, Kallika (2012)
Rice is among the cereals that share a leading role as important food sources for mankind. It is not only a staple food for a large part of the world population but also a main cash crop in the Thai economy. Of the total 24.86 million households in the Thai agriculture sector, 3.71 million represented paddy farmers. (Office of Agricultural Economics, 2010) Rice production in Thailand has increased over the past decade due mainly to the expansion of planting areas. However, the last few years saw a decline in planting areas and yields from 11.23 million hectares in 2007 to 11.10 million hectares in 2009. This could be attributable to the planting of energy crops and other cash crops in place of paddy. The high cost of inputs was another important problem confronting Thai farmers. As a result, the average yield in Thailand amounts to 2.88 metric tons per hectare, a comparatively lower capacity within each variety and among other rice producing countries. The objective of this study is to investigate technical efficiency and identify the factors affecting technical inefficiency of paddy farmers for the crop year 2009/2010 in the Central region of Thailand. Data collection was based on stratified random sampling from 384 farmers who used broadcasting method in operating their farms. Collected data was categorized into four sets of variables: 1) production variables, 2) demographic and socioeconomics variables, 3) agricultural extension variables, and 4) environmental variables. Both non-parametric (Data Envelopment Analysis: DEA) and parametric (Stochastic Frontier Analysis: SFA) techniques were applied in the analysis. The former explored the determinants for farm inefficiency through Tobit regression model, and the latter identified the factors influenced by inefficiency effect model by Battese and Coelli (1995). Descriptive statistic results showed that most farms are small-sized of about 4.70 hectares each. Of the total area, 75.30 percent were rented for cultivation. About 77.80 percent of production inputs were procured by credits while the rest were self-financed. Most farmers (77.50 percent) are male of about 51 years old in average. About 77.20 percent of the farmers received only compulsory education but had more than 30 years’ experience in rice farming. The technical efficiency level obtained by Data Envelopment Analysis varied between 0.30 to 100 percent. The mean technical efficiency equals to 51.60. This implied that on average, farmers could reduce their input use by 48.40 percent to enhance efficiency level. The empirical finding indicated that there was a positive relationship between farm efficiency and family labor as well as farm size. Stochastic Frontier Analysis ranged between 49.99 to 97.17 percent with the mean efficiency at 85.32 percent. Although 76.30 percent of farms showed their performances above 80 percent, hypotheses testing indicated that there was still inefficiency effect in rice farming. The factors which statistically and significantly contributed to higher performance were gender, farming experiences, land tenure, Good Agricultural Practices (GAP) and cropping intensity. In conclusion, technical efficiency can be different depending on which estimated techniques were used. Both DEA and SFA affirmed that there is an inefficiency effect on rice farming. However, farm efficiency level can be improved by reducing input use and eliminating the factors affecting technical inefficiency. Farmer should gain knowledge on Good Agricultural Practices (GAP) and adopt the GAP in their farm activities. Accessible linkages to extension officers should also be made available for continuous exchange of knowledge and experience, especially between successful farmers to general farmers in order to improve farm efficiency. In irrigated areas, government support should be provided to ensure that farmers can increase their planting capacity to more than once a year, and to use certified seeds which are high-yielding varieties in order to enhance their income and contribute to the overall rice production.